Acoustic correlates of female speech under stress based on /i/-vowel measurements. (22nd November 2017) - Tavi, Lauri
Abstract : The purpose of this article is to measure and evaluate commonly identified, yet rather inconsistent, acoustic correlates of speech under stress from authentic emergency call recordings. In this study, ten different acoustic parameters are measured from manually segmented /i/-vowels and hypotheses based on previous studies are statistically tested for a set of female emergency call recordings. The statistical analyses confirm that in comparison to the neutral speech group, the speech under stress group differs in fundamental frequency, shimmer, harmonicity, Hammarberg index, F1, F2, F3 and formant dispersion, which mostly supports the findings from previous studies. Conversely, jitter and vowel duration do not show any statistical difference between the speech under stress group and the neutral group. Furthermore, the results substantiate that stress recognition using different acoustic parameters is feasible from data sets as small as vowel segments; however, the effect of inter-speaker variation must not be underestimated. In future research, a stress detection model for telephone bandpass limited speech based on the optimal combination of acoustic parameters will be created.